The Association Between Perceived Risk of COVID-19, Psychological Distress, and Internet Addiction in College Students: An Application of Stress Process Model - Chang, Biru; Hou, Jianhua (Frontiers in Psychology, 2022)
The closed-off management of University during Covid-19 may be associated with an elevated odds of psychological and behavioral issues among college students. We aimed to use stress-process model to explore the potential mechanisms for this phenomenon. A total of 924 college students were recruited via posters, peer referral, and class attending. Among them, 82 (9%) were probable depression, and 190 (20.8%) were probable anxiety, 69 (7.5%) were internet addiction. Parallel mediation was used to test this theoretical model. For personal resources, perceived risk of Covid-19 was positively associated with psychological distress via negative coping style (β = 0.051) and internet addiction via negative coping style or self-esteem (β = 0.023 for negative coping style, β = 0.015 for self-esteem). For social resources, perceived risk of Covid-19 was positively associated with psychological distress and internet addiction via roommate relationship (β = -0.19 for psychological distress, β = -0.046 for internet addiction). Negative coping style and roommate relationship are possible psychological mechanisms linking perceived risk of Covid-19, psychological distress and internet addiction.